Avaliação têmporo-espacial do processo erosivo marginal dos córregos Mandacarú e da Romeira - Maringá-PR - Rigon, Bruno Tiago Contessotto (2010)
The dynamics of the landscape is changed as actions promoted by external means, accelerating and modifying certain standard natural. These changes are observed in the same morphological complex where the use and the occupation of the soil interfere accelerating the process of natural erosion. The basins of the stream Mandacarú and Romeira have different occupation of the ground being an urban and other rural. Using the method of the pins, the assessment of the bank erosion for both basins to demonstrate the occupation of the ground is an important variable for the loss of the bank in basins of small orders. The liquid flow the streams, concentration, transport of sediments, turbidity and the bank erosion was verified in this work. The results confirmed the hypothesis that the urban area with influence registered the largest values of the bank erosion. The lowest values registered in stream Mandacarú are more than stream Romeira. The urbanization without planning, mainly in basins of small order, added the rains, accelerates the process of the bank erosion making a lot of changes in the bed.